Evaluasi Program Model CIPP Pada Pembelajaran Mata Kuliah Bahasa Inggris di Sekolah Tinggi Ilmu Tarbiyah Darul Ulum Kubu Raya - Abdul Pandi; Siti Mania; Akbar Rasyid, Muhammad Nur (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2023)
This research aims to evaluate the CIPP (Context, Input, Process, Product) model program implemented at the Darul Ulum Kubu Raya Tarbiyah College of Science. This type of research uses qualitative. Sources of research data are English lecturers, deputy head of curriculum, and head of study program. data collection methods: observation, interviews and documentation. Based on the context component analysis, it can be said that the standard is that the name of the college is clearly visible, the number of students, lecturers and the facilities and infrastructure available can be said to be sufficient to carry out the English language learning process at the Darul Ulum Kubu Raya Tarbiyah College of Science so that it can be carried out well. . Based on the input evaluation, it can be said that students who are looking for knowledge, curriculum, teaching materials, lecturers, and learning facilities are tools that can help achieve a learning goal. This needs to be maintained and developed. Based on data analysis, it is stated that the learning process carried out has been fulfilled and meets the standards that have been set together and must be maintained throughout the learning process. And the learning results show that students at the Darul Ulum Kubu Raya Tarbiyah College of Science during the learning process for English courses can be said to be quite good or effective based on the value data obtained by the students.